Discourse Helplessness and Power Relations Women’s in The Film 7 Hearts 7 Love 7 Women Movie - Laode Jumaidin; Hasriani Amin; Darni (CV. Literasi Indonesia, 2022)
The film 7 hearts 7 love women discuss women who experience helplessness. The film tells the story of 7 women with various backgrounds, generations, professions, life problems, and romance. The film tells the story of women who take place around her, ranging from the lives of teenage girls who become pregnant out of wedlock, to prostitutes suffering from uterine cancer. This study aims to find out the forms of signs or symbols of female helplessness in the film 7 hearts 7 love 7 women. The research is carried out using qualitative descriptive analysis techniques. The theory used is the semiotics theory of Charles Sanders Pierce. Data collection techniques are observation, documentation, and literature studies. The data collected was then analyzed using semiotics theory by Charles Sanders Pierce method with three stages of analysis, namely representation, object, and interpretation. The results of this study show that there are several scenes and dialogue about the forms of signs of female helplessness in the film 7 hearts 7 love 7 women, such as domestic physical violence, sexual violence, women are not important in domestic decision-making, psychic violence, and being victimized in promiscuity.